Tracking Low-Frequency Variations in Land–Sea Water Mass Redistribution during the GRACE/GRACE-FO Era - Shanshan Deng; Zhenlong Jian; Yuxin Liu; Chushun Yi; Yi Chen; Wenxi Zhang (Remote Sensing, 2023)
Climate change has caused a widespread deduction in terrestrial water storage (TWS), leading to ocean water mass gains and sea level rises. A better understanding of how the land–sea water mass has been redistributed can help with the scientific response to climate change. However, there are few studies investigating the roles of the different physical processes involved in low-frequency land–sea water mass redistribution on a global scale. To address this issue, in this study, a comprehensive investigation was carried out with respect to the globally distributed key factors causing low-frequency ocean mass anomalies during the period 2004–2021. Global water mass redistribution data, derived from GRACE/GRACE-FO satellite gravity and surface wind and sea-surface temperature data from ERA5 reanalysis, were employed, and the empirical orthogonal function, maximum covariance analysis, and sea-level equation approaches were used. The results show that the long-term trend and decadal-like fluctuation are two major components of the low-frequency land–sea water mass redistribution. The wind-forcing dynamic processes significantly drive the anomalies near the North Indian Ocean, North Atlantic Ocean, South Pacific Ocean, and some marginal seas, where variance explanations range from 30% to 97%. After removing the ocean dynamics, the residual ocean mass anomaly is mostly explained by sea-level fingerprints (SLFs), especially in the open ocean. The 25th, 50th, and 75th percentiles of the SLF-explained variances in all ocean grids are 59%, 72%, and 82%, respectively. Some non-negligible noise, located in seismic zones, was also found, suggesting the misestimation of seafloor deformation resulting from earthquakes in the GRACE/GRACE-FO data processing. These findings may improve our understanding of the long-term anomalies in regional and global sea levels.